Parents' Psychological Aspect in Caring for the Child During COVID-19 Pandemic - M. Hasinuddin; Rusana Rusana; Ulva Noviana; Heni Ekawati; Nurul Aini; Sandeep Poddar (Universitas Airlangga, 2021)
Introduction: COVID-19 is unprecedented, especially for parents with children aged 2-12 years old who are prone to infection due to their activities. The psychological condition of parents will be affected as they are worried about their children being infected with COVID-19.Methods: This study aims to identify and analyse the psychological aspects of parents who are caring for children during the COVID-19 pandemic.Results: The results showed that as many as 236 parents (80.9%) showed an emotional anxiety response. The social reaction to the COVID-19 situation was more likely to be a positive response (73.8%) rather than a negative response.Conclusion: The reactions that occur in parents who have pre-school and school-aged children regarding the COVID-19 were anxiety and worry. Reactions arise due to the information obtained being less verifiable, namely social media.